Epistemological Critique and Framework for Islamic Parenting Research in the Digital Era - Putri, Ellyana Ilsan Eka; Masruroh, Fitriatul (INCARE, International Journal of Educational Resources, 2025)
This study analyzes the philosophical framework, thematic evolution, and research inconsistencies in the global literature about Islamic parenting. This study employs bibliometric analysis, utilizing VOSviewer and Biblioshiny on the Scopus database, to examine publishing patterns, regional distribution, and theme mapping. The findings indicate that (1) Indonesia leads global knowledge production, resulting in an Indonesian-centric bias; (2) there has been a shift in research focus, transitioning from a school-based paradigm (2014-2018) to Family Internalisation (2019-2021) and currently to Digital Resilience (2022-2024); and (3) there exists a pronounced pedagogical hegemony, with parenting being examined more within the framework of Early Childhood Education (PAUD) than Clinical Psychology. Consequently, the forthcoming study ought to transition its emphasis from normative-educational narratives to clinical investigations about mental health and preventive measures in the digital era.